2019
DOI: 10.1093/geront/gnz075
|View full text |Cite
|
Sign up to set email alerts
|

A Preference-Based Model of Care: An Integrative Theoretical Model of the Role of Preferences in Person-Centered Care

Abstract: Knowledge of individuals’ everyday preferences is a cornerstone of person-centered care (PCC). Initial evidence demonstrates the positive impact of honoring preferences in care for older adults receiving long-term services and supports (LTSS). Yet, the mechanisms through which preference-based care affects individual well-being remain poorly understood. This article proposes a theoretical model of PCC entitled the Preference-Based Model of Care that integrates the Theory of Human Motivation, Self-determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 27 publications
2
61
0
2
Order By: Relevance
“…Frameworks that focus on behavioral symptoms operate from a deficit perspective and may not be appropriate for modeling positive outcomes such as affect balance. Strong conceptual frameworks from a strength perspective are needed to guide future research on affect balance and are being developed (Van Haitsma et al, 2019). More research is needed to design and evaluate staff communication interventions and their effect on affect balance.…”
Section: Discussionmentioning
confidence: 99%
“…Frameworks that focus on behavioral symptoms operate from a deficit perspective and may not be appropriate for modeling positive outcomes such as affect balance. Strong conceptual frameworks from a strength perspective are needed to guide future research on affect balance and are being developed (Van Haitsma et al, 2019). More research is needed to design and evaluate staff communication interventions and their effect on affect balance.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of recreational preference congruence has been put forward as one way to operationalize and measure person-centered care. Recreational preference-congruence is the match between important resident preferences for how they spend their leisure time and attendance/ engagement with activities offered, which is hypothesized to lead to greater well-being (VanHaitsma et al, 2020). Methods of tracking recreational preference congruence have been developed and tested (Van Haitsma et al, 2016) and prior research has found that having more important preferences is associated with greater preference-congruent care.…”
Section: Introductionmentioning
confidence: 99%
“…As such, assessing patient preferences is now acknowledged as an essential element of patient-centered healthcare [8] since it encompass all aspects of healthcare interventions on patients' well-being [7,9].…”
Section: Introductionmentioning
confidence: 99%